Epidemiological, ecological and clinico-laboratory characteristics of hemorrhagic fever with renal syndrome in Saint-Petersburg and suburb - V. V. Nechaev; I. I. Yarovayа; I. V. Gorbunova; O. V. Meo; I. P. Fedunjk; A. P. Chmir; N. C. Litvinova; I. C. Chinzeria; N. E. Chunaeva (Журнал инфектологии, 2021)
The goal is to identify the epidemiological, territorial-epidemiological, environmental, clinical and features of hemorrhagic fever with renal syndrome in order to improve epidemiological surveillance in a large metropolis of the Northwestern Federal District.Materials and methods. An epidemiological analysis of cases of hemorrhagic fever with renal syndrome in St. Petersburg for 2005–2019 was carried out and the clinical and epidemiological characteristics of 135 patients hospitalized in the S.P. Botkin Clinical Infectious Disease Hospital were studied. 70 patients identified combined HFRS diseases associated with other pathogens of viral and bacterial nature. An epidemiological analysis of cases of hemorrhagic fever with renal syndrome in St. Petersburg for 2005–2018 and long-term monitoring of the zoological, epizootological state of small mammals in several districts of St. Petersburg and its suburbs were carried out. The clinical and epidemiological characteristics of 135 patients were studied, of which 70 patients identified combined hemorrhagic fever with renal syndrome diseases associated with other pathogens of a viral and bacterial nature. To assess the epizootological situation, trapped rodents were examined for the presence of viral antigen and antibodies using the method of indirect immunofluorescence with the Xantagnost diagnosticum and enzymelinked immunosorbent assay.Results. The long-term dynamics of the incidence rate in St. Petersburg had a fluctuant rising character with two peaks. The proportion of diseases during the first rise was 11,5%, the second – 44,2% of the long-term incidence. Men prevailed in the age groups of 20-49 years without changes in periods. The proportion of women 20–49 years old was 20,7%, increased to 52,8 % in age groups over 50 years old. When distributed by month in a period of high incidence, the seasonal rise began in September with a peak in October. Infection with hemorrhagic fever with renal syndrome patients – residents of the city occurred mainly (with 35.5%), in the nearby territories of the Northwestern Federal District with 8.9% - in remote areas and with 5,9% in the countries of near and far abroad. The epidemiological situation in places of temporary residence and infection of people was characterized by an increase in the number of small mammals (redbacked voles) and, in particular, infection from 2,9 to 4,4%. Hemorrhagic fever with renal syndrome diseases occurred in the form of moderate severity in 94,4% cases. Severe forms were found in only 5,6% of cases. In the structure of combined infection in 25,9–22,3%, there was a combination of hemorrhagic fever with renal syndrome with gastroenterocolitis and influenza, serologically confirmed. In 17,6% of cases, hemorrhagic fever with renal syndrome was combined with other zoonoses (Lyme disease, tick-borne encephalitis, pseudotuberculosis, leptospirosis, tularemia), in 17,6% with of various etiologies. The presence of combinations of hemorrhagic fever with renal syndrome with other infections complicates the clinical diagnosis.